2014
DOI: 10.5414/cn108119
|View full text |Cite
|
Sign up to set email alerts
|

The iron-based phosphate binder PA21 has potent phosphate binding capacity and minimal iron release across a physiological pH range in vitro

Abstract: These studies demonstrate that PA21 has potent phosphate binding capacity and low iron release over a physiologically relevant pH range in the GI tract. These features indicate PA21 could be an effective alternative phosphate binder for CKD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 23 publications
(27 reference statements)
2
36
0
1
Order By: Relevance
“…Phosphate binding occurs across a wide range of stomach pH, with a peak at pH 2.5. 40 Common adverse effects include diarrhoea and change in stool colour. There was no evidence of iron accumulation in a phase III extension study.…”
Section: Sucroferric Oxyhydroxidementioning
confidence: 99%
“…Phosphate binding occurs across a wide range of stomach pH, with a peak at pH 2.5. 40 Common adverse effects include diarrhoea and change in stool colour. There was no evidence of iron accumulation in a phase III extension study.…”
Section: Sucroferric Oxyhydroxidementioning
confidence: 99%
“…Sucroferric oxyhydroxide (SFOH; VELPHORO®; previously known as PA21) is a novel, iron-based phosphate binder that has been shown in vitro to have a high phosphate-binding capacity and low iron release [8]. In an open-label, randomized, Phase 3, 24-week study, SFOH demonstrated similar efficacy and tolerability to SEV carbonate (Renvela®) but with a lower pill burden [9].…”
Section: Introductionmentioning
confidence: 99%
“…49 Under experimental conditions reproducing administration of the drug on an empty stomach and full stomach across the physiological pH range, sucroferric oxyhydroxide demonstrated to efficiently bind phosphate at every pH value and release more iron at the lowest pH in the absence of phosphate, whereas the amount of iron freed resulted in being much lower when phosphate was present and minimal with pH ranging from 2.5 to 8.5. 45 In more detail, in vitro experiments showed that iron release was equal to 0.3% at higher pH values while it amounted to a maximum of 6.3% at a pH of 1.2-1.5; the last percentage went up to 67% using an artificial gastric juice without phosphate. 49 It follows that iron uptake is greater in the fasting state and that, consequently, sucroferric oxyhydroxide must be taken with food.…”
mentioning
confidence: 99%